Developmental Programming: State-of-the-Science and Future Directions: Summary from a Pennington Biomedical Symposium - Sutton, Elizabeth F. (Obesity (Silver Spring), 2016)
OBJECTIVE: On December 8–9, 2014, the Pennington Biomedical Research Center convened a scientific symposium to review the state-of-the-science and future directions for the study of developmental programming of obesity and chronic disease. The objectives of the symposium were to discuss: (i) past and current scientific advances in animal models, population-based cohort studies and human clinical trials, (ii) the state-of-the-science of epigenetic-based research, and (iii) considerations for future studies. RESULTS: The overarching goal was to provide a comprehensive assessment of the state of the scientific field, to identify research gaps and opportunities for future research in order to identify and understand the mechanisms contributing to the developmental programming of health and disease. CONCLUSIONS: Identifying the mechanisms which cause or contribute to developmental programming of future generations will be invaluable to the scientific and medical community. The ability to intervene during critical periods of prenatal and early postnatal life to promote lifelong health is the ultimate goal. Considerations for future research including the use of animal models, the study design in human cohorts with considerations about the timing of the intrauterine exposure and the resulting tissue specific epigenetic signature were extensively discussed and are presented in this meeting summary.